Governing human life: (bio)politics, knowledge and borders in global drug policy - Ditrych, Ondrej (Palgrave Macmillan, 2023)
Chapter 1. Introduction: A Case for a Critical Biopolitical Analysis of the Global Drug Control -- Chapter 2. Drug Control Dispositif, State of Exception and Democracy -- Chapter 3. Which Knowledge Deserves to Be Named Knowledge: The Place for Science and Evidence in Drug Policy -- Chapter 4. Migrants, Substances, and Borders: The Case of the Spanish Southern Border -- Chapter 5. Conclusion. .